2019
DOI: 10.1002/jcb.28447
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow stromal cells transplantation promotes the resolution and recanalization of deep vein thrombosis in rabbits through regulating macrophage infiltration and angiogenesis

Abstract: This study aims to validate whether bone marrow stromal cells (BMSCs) transplantation could promote the resolution and recanalization of deep vein thrombosis (DVT) and to explore the underlying mechanism. The right hind femoral vein was embolized to establish the DVT rabbit model. BMSCs from New Zealand white rabbits were isolated and identified, and then injected into DVT rabbits. After that, the extent of angiogenesis was determined by the amount of capillaries that were positive for antibody against vWF. Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…As reported, monocyte recruitment plays a pivotal role in thrombus lysis; endogenous MCP-1 levels increased in spontaneously dissolving venous thrombi, and the injection of MCP-1 into the thrombosed tissue enhances thrombus lysis, according to previous research studies ( Humphries et al, 1999 ; Ali et al, 2006 ; Gutmann et al, 2020 ). Zhang et al reported the subsequent elevation experiment on rabbits, where they discovered that increased MCP-1 protein expression caused by bone marrow MSC transplantation promoted the regression and recanalization of DVT ( Zhang et al, 2019 ). Georgakis et al discovered that higher MCP-1 levels were related to an increased risk of cardioembolic arterial thrombosis in stroke, as well as mortality ( Georgakis et al, 2019a ; Georgakis et al, 2019b ; Georgakis et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…As reported, monocyte recruitment plays a pivotal role in thrombus lysis; endogenous MCP-1 levels increased in spontaneously dissolving venous thrombi, and the injection of MCP-1 into the thrombosed tissue enhances thrombus lysis, according to previous research studies ( Humphries et al, 1999 ; Ali et al, 2006 ; Gutmann et al, 2020 ). Zhang et al reported the subsequent elevation experiment on rabbits, where they discovered that increased MCP-1 protein expression caused by bone marrow MSC transplantation promoted the regression and recanalization of DVT ( Zhang et al, 2019 ). Georgakis et al discovered that higher MCP-1 levels were related to an increased risk of cardioembolic arterial thrombosis in stroke, as well as mortality ( Georgakis et al, 2019a ; Georgakis et al, 2019b ; Georgakis et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several mechanisms are involved in this function, (1) MSCs reduce apoptosis of vascular endothelial cells and subsequently the vessel injury and disseminated intravascular coagulation (DIC) through decreasing the expression of pro-inflammatory cytokines such as TNF-α, IFN-γ, IL-6. (2) Suppression of immune cells, including T-cytotoxic lymphocytes, NK cells, and B cells by MSCs prevent the formation of microthrombi fibrin and also, (3) MSCs alter the differentiation of macrophages polarization toward M2 phenotype, which promotes neovascularization and tissue repair (Zhang et al 2019 ; Jamshidi et al 2021 ).…”
Section: Mscs and Msc-derived Exosomes: A Comparison Of Efficiency In Covid-19 Treatmentmentioning
confidence: 99%
“…MSCs induce vascular-like structures through the infiltration of macrophages in thrombosis sites. The macrophages inside thrombosis induce 1) proliferation and migration of endothelial cells, 2) lysis of extracellular matrix, 3) secreting angiogenesis factors such as VEGF and basic fibroblast growth factor (bFGF) [123]. It seems that administration of MSCs may reduce coagulation complications in COVID-19 by controlling Haemostasis factors.…”
Section: Effects Of Mscs In Coagulationmentioning
confidence: 99%